Weblog: How far is it effective as an online communication tool to students? / Naemah Abdul Wahab, Wan Anisha Wan Mohammad and Azlina Mohd Mydin - Abdul Wahab, Naemah; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina (2008)
Online communication is a communication via the Internet from anywhere, at any time or place using various communication tools. There are many forms of online communication tools such as electronic mail (e-mail), video-conferencing, discussion groups, bulletin boards, Internet forums, weblogs, instant messaging and real-time chat. One of the web-based communications technologies that have turned into a widespread popularity is weblogs. Weblogs or blogs are frequently updated webpages with posts typically in reverse- chronological order. It varies widely in nature and content ranging from politics, technology and recently grown in popularity on personal themes. Since many youth mainly students are choosing blogs as a means to communicate online, therefore, this research will be done in order to identify whether web blogging can be an effective online communication tool to students. Due to that, a comparison of the students from various fields of study will be done in order to identify their views and opinions on the effectiveness of blogs for online communication.